Pendidikan Orang Dewasa dan Ketimpangan Sosial - Dhea Pramedia Wardani; Fawzia Sheryl Desideria; Anjani Anjani; Sofia Wulandari (Lembaga Pengembangan Kinerja Dosen, 2026)
Adult education is a strategic component of lifelong learning that plays a crucial role in improving human resource quality while reducing social inequality. However, the reality in Indonesia shows that equal access and quality of adult education remain structural challenges, particularly between urban and rural areas. This article aims to examine the dynamics of adult education from an andragogical perspective and to analyze the structural, socio-economic, and digital factors that create inequality in adult learning access. This study employs a narrative literature review approach, examining relevant journal articles, books, and policy documents on adult education, andragogy, and social inequality. The findings indicate that inequality in adult education is shaped by three main dimensions: uneven infrastructure distribution, economic and gender disparities, and a digital divide that generates new barriers in the form of limited infrastructure, digital literacy, and content relevance. This study concludes that an inclusive andragogical approach and policies that focus not only on expanding access but also on ensuring equal quality and psychosocial support are needed to break the cycle of educational inequality and promote sustainable social development.